The Effects of MPL-Ligand, Interleukin-6 and Interleukin-11 on Megakaryocyte and Platelet Alpha-granule Proteins - Philipp, Claire S.; Remmler, Jill; Zucker-Franklin, Dorothea (Thrombosis and Haemostasis, 1998)
Thrombopoietin (Mpl ligand), interleukin-6 (IL-6), and interleukin-11 (IL-11) differ in their effects on megakaryocyte maturation and development. In the present study, the impact of these thrombocytopoietic cytokines on biochemical and structural granule and membrane components was examined. Western blotting was performed on equivalent amounts of isolated megakaryocyte or platelet protein and the relative intensities of the enhanced chemiluminescent-visualized bands were quantitated by densitometry. Megakaryocyte growth and development factor (MGDF), a recombinant thrombopoietin-related molecule, significantly increased megakaryocyte fibronectin (72%), thrombospondin (55%), von Willebrand factor (28%) and p-selectin (CD62p) (37%) when compared to equivalent amounts of protein from saline-treated controls (p < 0.01). Megakaryocyte fibrinogen was not increased. Ultrastructurally, there was a marked increase in ribosomes and rough endoplasmic reticulum even in mature-appearing megakaryocytes. Platelets from MGDF-treated mice showed small increases in fibronectin (8%), and CD62p (18%), but did not show increases in other measured α-granule proteins. Neither IL-6 nor IL-11 increased megakaryocyte or platelet α-granule proteins over levels observed in saline controls. IL-11 treated megakaryocytes, while also exhibiting an increase in ribosomes, were characterized by prominent cytoplasmic fragmentation. The study demonstrates the impact of Mpl ligand in increasing synthesized megakaryocyte α-granule proteins and of IL-11 in promoting megakaryocyte fragmentation.